Lasertechnik. - Dohlus, Rainer (De Gruyter Studium., 2015)
This textbook is intended for students in their third and fourth semesters of study in engineering at German institutes of applied sciences. It imparts introductory knowledge on laser technology, the fundamentals of light formation, and laser light sources, and also covers examples of laser applications. There are many practice exercises with solutions.